Capillary infiltration of hexadecane in packed SiC powder and in SiC/SiC preforms: Pore description and calculation of molten Si infiltration. Issue 6 (1st May 2016) - Marchais, A.; Roger, J.; Le Petitcorps, Y.
Abstract: A SiC/SiC–Si composite can be synthesised by molten silicon infiltration in a SiC preform impregnated with a slurry of SiC powder. The kinetics of molten silicon infiltration in such a porous material are unknown, and the experimental measurement is complex. The calculation of the rise kinetics for a liquid in a porous material is possible by applying the Washburn modified equation with an accurate description of the pores. The monitoring of the mass and front height variations during hexadecane infiltration in a submicronic SiC packed powder and in a preform filled with a SiC powder was used to characterize the porosity. In the case of a fibrous preform, the residual porosity is composed of inter-grain pores and cracks formed during the drying of the slurry. The results of this study suggest that the liquid progresses first in the inter-grain porosity of the powder. The rise kinetics of molten silicon into a preform were then evaluated by calculation based on the pore description obtained from hexadecane capillary infiltration experiments.